Elder mistreatment in South Asian communities: a review of the literature. Issue 5 (10th December 2018) - Talpur, Ashfaque Ahmed; Ryan, Tony; Ali, Parveen; Hinchliff, Sharron
Abstract : Purpose: The purpose of this paper is to perform a review of the literature of empirical studies on elder mistreatment (EM) in South Asians, and to discuss key implications for policy, practice and research. Design/methodology/approach: For this review, multiple electronic databases in the international health and social science were searched and supplemented by grey literature and cross-references. Quality of papers was assessed by two authors against the standard checklists. Findings: In total, 16 studies met the inclusion criteria of this review, of which 11 were cross-sectional design, and only six of them used standard instruments to measure EM. The prevalence estimates of overall EM retrieved from general population-based studies ranged from 9.3 per cent in India to 49.1 per cent in Nepal. Age, gender, residential settings, socioeconomic status, health, education, and social structures and processes were key risk factors for EM in South Asian communities. Reporting and action taking were culturally rooted. Originality/value: While the review is not systematic, there are limitations associated with the paper in covering the diverse range of databases and studies. However, this review provides a valuable synthesis of the empirical papers on the incidence, culturally specific risk factors and reporting trends of EM in South Asians. Additionally, the review presents the papers evaluated for a quality to ensure the validity of empirical data. Finally, the review includes several implications for policy, practice and future research on EM which may ultimately contribute in improving the health and wellbeing of elder South Asians.